The Goals and Tasks of Music Literacy Classes in General Education Schools - Abidinovich Khushnudbek Khodjayev (Journal of Higher Education and Academic Advancement, 2024)
in the lesson "Musical tradition and culture" all activities are logically interconnected under a certain topic, as a result of which the unity of the lesson is created. Music literacy is important as a theoretical unifying activity of all activities.